A Strategy for Development - Stern, Nicholas (Washington, DC: World Bank, 2013)
This book is about a collection of speeches -all delivered since Nicholas Stern became Chief Economist of the World Bank in July 2000- they reflect insights that Mr. Stern has gained over more than three decades of study and work in development economics. Together they provide an analysis of development experience and an agenda for action in coming years. In his introduction the author explains the evolution of his ideas, starting with early work in Africa and India, within the larger context of changes in development thinking and strategy. The speeches that follow draw on his varied experience and on the research findings and operational experience of the World Bank. The first speech provides and overview of the past five decades of development. Speeches that follow explore current development issues in India, Indonesia, Pakistan, and China. A strategy for development is then outlined; building an economic climate that facilitates investment and growth, and empowering poor people to participate in that growth. A concluding speech examines the role of the international financial institutions in promoting investment and overcoming poverty.